Whole-genome comparison using complete genomes from Campylobacter fetus strains revealed single nucleotide polymorphisms on non-genomic islands for subspecies differentiation - Ong, Chian Teng; Blackall, Patrick. J.; Boe-Hansen, Gry B.; deWet, Sharon; Hayes, Ben J.; Indjein, Lea; Korolik, Victoria; Minchin, Catherine; Nguyen, Loan To; Nordin, Yusralimuna; Siddle, Hannah; Turni, Conny; et al. (Frontiers in Microbiology, 2024)
Introduction Bovine Genital Campylobacteriosis (BGC), caused by Campylobacter fetus subsp. venerealis, is a sexually transmitted bacterium that significantly impacts cattle reproductive performance. However, current detection methods lack consistency and reliability due to the close genetic similarity between C. fetus subsp. venerealis and C. fetus subsp. fetus. Therefore, this study aimed to utilize complete genome analysis to distinguish genetic features between C. fetus subsp. venerealis and other subspecies, thereby enhancing BGC detection for routine screening and epidemiological studies. Methods and results This study reported the complete genomes of four C. fetus subsp. fetus and five C. fetus subsp. venerealis, sequenced using long-read sequencing technologies. Comparative whole-genome analyses (n = 25) were conducted, incorporating an additional 16 complete C. fetus genomes from the NCBI database, to investigate the genomic differences between these two closely related C. fetus subspecies. Pan-genomic analyses revealed a core genome consisting of 1,561 genes and an accessory pangenome of 1,064 genes between the two C. fetus subspecies. However, no unique predicted genes were identified in either subspecies. Nonetheless, whole-genome single nucleotide polymorphisms (SNPs) analysis identified 289 SNPs unique to one or the C. fetus subspecies. After the removal of SNPs located on putative genomic islands, recombination sites, and those causing synonymous amino acid changes, the remaining 184 SNPs were functionally annotated. Candidate SNPs that were annotated with the KEGG “Peptidoglycan Biosynthesis” pathway were recruited for further analysis due to their potential association with the glycine intolerance characteristic of C. fetus subsp. venerealis and its biovar variant. Verification with 58 annotated C. fetus genomes, both complete and incomplete, from RefSeq, successfully classified these seven SNPs into two groups, aligning with their phenotypic identification as CFF (Campylobacter fetus subsp. fetus) or CFV/CFVi (Campylobacter fetus subsp. venerealis and its biovar variant). Furthermore, we demonstrated the application of mraY SNPs for detecting C. fetus subspecies using a quantitative PCR assay. Discussion Our results highlighted the high genetic stability of C. fetus subspecies. Nevertheless, Campylobacter fetus subsp. venerealis and its biovar variants encoded common SNPs in genes related to glycine intolerance, which differentiates them from C. fetus subsp. fetus. This discovery highlights the potential of employing a multiple-SNP assay for the precise differentiation of C. fetus subspecies.